Optimising health outcomes via pharmacist delivered telehealth medicines management: a systematic review. (26th October 2020) - Lowry, Samuel J.; Kay, Charlotte N.; Marsom, Erica N.; Park, Joon Soo; Poole, Susan; Page, Amy T.
Abstract: Background: Pharmacist‐led telehealth is an innovative service delivery model that may provide an alternative mode of care. It remains unclear how surrogate markers of health conditions differ when pharmacist services are delivered via telehealth compared to usual care. Aims: To assess if pharmacist‐led telehealth interventions alter surrogate markers of health conditions. Methods: Pharmacist‐led telehealth interventions compared to another active intervention for people using one or more regular medicines were included that reported surrogate markers of health conditions. Scopus, Embase, Medline and CINAHL were searched from inception to May 2020 to identify randomised controlled trials. Researchers screened articles to identify eligible studies, then data were extracted using a standardised data collection sheet. Quality assessment was undertaken using the Cochrane risk of bias tool. Data were reported as risk ratio and mean difference with corresponding 95% confidence intervals. Results: Of 1896 titles identified, 11 studies met the inclusion criteria. Telehealth interventions by pharmacists consisted of multifaceted interventions with contact over differing time durations. Some blood pressure and oral anticoagulation clinical outcomes were improved in the pharmacist‐led telehealth group compared to the control group. However, the majority of outcomes were similar in both groups. Conclusion: This study identified that pharmacist‐led telehealth interventions for a select range of chronic health conditions provides an acceptable adjunct to usual care and results in similar health outcomes for surrogate markers when compared to usual care.